Habermas vs Fish – a question about the possibility of intercultural agreement - Wieczorkowski, Michał (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The purpose of the paper is to analyze the thesis that an agreement between representatives of two different cultures can and should be reached at a theoretical level. The author tries to verify the Theory of Communicative Action proposed by Jürgen Habermas in the light of philosophical reflections of American neopragmatist Stanley Fish. Habermas is one of the most important and widely read social theorists in the post-Second World War era. He is also one of the authors of the concept of deliberative democracy, which holds that, for a democratic decision to be legitimate, it must be preceded by authentic deliberation – disinterested exchange of reasons – not merely the aggregation of preferences that occurs in voting. The foundation of deliberative democracy is, according to the German thinker, a communicative action based on communicative rationality. Stanley Fish, in turn, is one of the most eminent American philosophers of the twentieth and twenty-first centuries. The main area of his scientific activity is the theory of literature, law, and history. In the course of his reflections, Fish constructed the concept of an interpretative communities, which implies an original view on the nature of the process of cognition, status of human convictions or beliefs, nature of communication situation and capabilities of theory. The final conclusion stemming from the reflection on Fish’s philosophy explains why Habermas’ theory is not an adequate tool to reach an intercultural agreement.
Keywords: communicative action; interpretive communities; intercultural agreement; neopragmatism